"Friendly racism" and white guilt: midwifery students' engagement with Aboriginal content in their program - Thackrah, Rosalie; Thompson, Sandra (Forum on Public Policy, 2013)
Since 2011, all first year students in a health sciences faculty at a university in Western Australia complete a compulsory (half) Unit titled Indigenous Cultures and Health. The Unit introduces students to Aboriginal and Torres Strait Islander history, diversity, cultural protocols, social structures, patterns of communication, contemporary policies and their implications for health professionals. It also invites students to reflect on the own social andcultural backgrounds and consider factors that shape their worldviews. The broader intent of the Unit is for students to commence the journey towards ‘Indigenous cultural competency’. This paper focuses upon findings from 12 weeks (24 hours) of classroom observations conducted in July-October 2012 with midwifery students enrolled in this Unit. It also explores data from comprehensive pre-and post-Unit questionnaires, together with findings from student and staff interviews. Observations, survey and interview data form part of a larger, mixed method study investigating culturally secure practice in midwifery education and ultimately service provision for Aboriginal women. Findings draw attention to strategies employed by teaching staff and students to create a safe learning environment, emotional responses and indicators of receptivity and resistance by students to Aboriginal content, the development of sophisticated critical thinking, and the uneasy, unnamed tension that hovered in the classroom and remained unresolved throughout the semester.